2004
DOI: 10.1002/cbdv.200490089
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Cytotoxicity, and Apoptosis Induction in Human Tumor Cells by Geiparvarin Analogues

Abstract: A series of geiparvarin analogues modified on the unsaturated alkenyloxy bridge, where a H-atom replaced the 3'-Me group, were synthesized and evaluated against a panel of human tumor cell lines in vitro. These compounds demonstrated a stronger increase in growth inhibitory activity when compared to the parent compound geiparvarin (8). In particular, the activity increased even further in the series of demethylated compounds when a Me substituent in the coumarin moiety is introduced. On the contrary, the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Thus MCF7-MDR cells are known to possess both efflux pumps as well as increased levels of glutathione peroxidase activity. [17] In agreement with our previous results [8] in which we showed that 1 and 2 a retain activity in multidrug-resistant cells, the new compounds also proved to be fully inhibitory to these resistant cell lines, as shown in Table 2, suggesting that they are not subject to the pump-mediated efflux of antitumor drugs.…”
Section: Effect Of Geiparvarin a C H T U N G T R E N N U N G Derivatisupporting
confidence: 93%
See 3 more Smart Citations
“…Thus MCF7-MDR cells are known to possess both efflux pumps as well as increased levels of glutathione peroxidase activity. [17] In agreement with our previous results [8] in which we showed that 1 and 2 a retain activity in multidrug-resistant cells, the new compounds also proved to be fully inhibitory to these resistant cell lines, as shown in Table 2, suggesting that they are not subject to the pump-mediated efflux of antitumor drugs.…”
Section: Effect Of Geiparvarin a C H T U N G T R E N N U N G Derivatisupporting
confidence: 93%
“…Optical activity was measured with a Jasco DIP-370 digital polarimeter (l = 589 nm). Compounds (R,S)-12, [8] 17, [31] 18, [31] and 19 [32] were obtained as reported. Silica gel plates (Merck F 254 ) and silica gel 60 (Merck 230-400 mesh) were used for analytical TLC and column chromatography, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Coumarin derivatives, naturally occurring or synthetic, exhibit a broad range of biological activities [14][15][16][17][18][19] including anticoagulant, antibiotic, antifungal, antipsoriasis, cytotoxic, anti-HIV, anti-inflammatory, antioxidant, antithrombin etc. The geiparvarin (VIII) and their derivatives exhibit antitumorial activity 20,21 and they also appeared as MAO-B inhibitors 22 . The auraptene (IX) is a chemopreventative agent against different kinds of cancer and an antiiflammatory agent 23 .…”
Section: Introductionmentioning
confidence: 99%